Dynamic 11C-PiB PET Shows Cerebrospinal Fluid Flow Alterations in Alzheimer Disease and Multiple Sclerosis - Schubert, Julia J; Veronese, Mattia; Marchitelli, Livia; Bodini, Benedetta; Tonietto, Matteo; Stankoff, Bruno; Brooks, David J; Bertoldo, Alessandra; Edison, Paul; Turkheimer, Federico E (The Journal of nuclear medicine (1978), 2019)
Cerebrospinal fluid (CSF) plays an important role in solute clearance and maintenance of brain homeostasis. 11C-Pittsburgh compound B (PiB) PET was recently proposed as a tool for detection of CSF clearance alterations in Alzheimer disease. The current study investigates the magnitude of 11C-PiB PET signal in the lateral ventricles of an independent group of Alzheimer and mild cognitive impairment subjects. We have also evaluated multiple sclerosis as a model of disease with CSF clearance alterations without amyloid-β tissue accumulation. Methods: A set of 11 Alzheimer and 12 mild cognitive impairment subjects and a set of 20 multiple sclerosis subjects with matched controls underwent MRI and dynamic 11C-PiB PET. Lateral ventricle regions of interest were generated manually from MRI data. PET data were analyzed using cerebellum or a supervised reference region for the Alzheimer and multiple sclerosis data sets, respectively. The magnitude of 11C-PiB signal in the lateral ventricles was calculated as area under the curve from 35 to 80 min and SUV ratio (SUVR) from 50 to 70 min. Compartmental modeling analysis was performed on a separate data set containing 11 Alzheimer and matched control subjects; this analysis included an arterial input function, to further understand the kinetics of the lateral ventricular 11C-PiB signal. Results: ANOVA revealed significant group differences in lateral ventricular SUVR across the Alzheimer, mild cognitive impairment, and healthy control groups (P = 0.004). Pairwise comparisons revealed significantly lower lateral ventricular SUVR in Alzheimer subjects than in healthy controls (P < 0.001) or mild cognitive impairment subjects (P = 0.029). Lateral ventricular SUVR was significantly lower in multiple sclerosis subjects than in healthy controls (P = 0.008). Compartmental modeling analysis revealed significantly lower uptake rates of 11C-PiB signal from blood (P = 0.005) and brain tissue (P = 0.004) to the lateral ventricles and significantly lower 11C-PiB signal clearance out of the lateral ventricles (P = 0.002) in Alzheimer subjects than in healthy controls. Conclusion: These results indicate that dynamic 11C-PiB PET can be used to observe pathologic changes in CSF dynamics. We have replicated previous work demonstrating CSF clearance deficits in Alzheimer disease associated with amyloid-β deposits and have extended the observations to include ventricular CSF clearance deficits in mild cognitive impairment and multiple sclerosis.